Comparative efficacy of different durations and dosages of vonoprazan and amoxicillin dual therapy: a network meta-analysis of randomized controlled trials - Feng-yi Wei; Zhen-peng Huang; Sha Nie; Ru-jie Gao (Frontiers in Medicine, 2026)
Background The combination of vonoprazan and amoxicillin (VA) has been shown to be effective in eradicating Helicobacter pylori infection; however, the optimal treatment duration and dosage are yet to be determined. Methods A systematic literature search of PubMed, Embase, and China National Knowledge Infrastructure was performed to identify randomized controlled trials (RCTs) comparing different durations of VA dual therapy or comparing this dual therapy with bismuth-containing quadruple therapy (BQT). All trials were conducted in China. A Bayesian network meta-analysis was used to evaluate the eradication rates and incidence of adverse events across different treatment regimens. Results Thirty-eight randomized controlled trials were ultimately included in the analysis. Network meta-analysis revealed that both the 14- and 10-day VA regimens achieved higher eradication rates compared with BQT, with odds ratios (OR) of 1.7 [ 95% credible interval ( CrI ) 1.3–2.1] and 1.4 ( 95% CrI 1.1–2.0), respectively. The 7-day regimen did not yield a difference in eradication rate compared with BQT ( P > 0.05). All VA dual therapy regimens were associated with lower rates of adverse events than those for BQT. Among patients receiving the 14-day VA dual therapy regimen, there was no difference in eradication rates between the high- and low-dose groups. The low-dose 14-day regimen was associated with higher eradication outcomes than the low-dose 10-day regimen. No significant differences in adverse event rates were observed between the various dosage groups. Conclusion The 14-day low-dose VA dual regimen offered a favorable balance between efficacy and safety, suggesting that it may be a promising option for H. pylori eradication. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420261284331 , identifier: CRD420261284331.